Subclinical inflammation, endothelial dysfunction and atrial electrical remodeling in early-onset paroxysmal atrial fibrillation without comorbidities - Ülgen Kunak, Ayşegül; Kunak, Tolga; Bayraktar, Ali; Aytemir, Kudret (Acta Medica, 2026)
Objective: Early-onset paroxysmal atrial fibrillation (PAF) in individuals without conventional cardiovascular risk factors has traditionally been labeled as “lone AF.” Recent evidence suggests that subtle structural, electrical, and functional abnormalities may still exist. This study evaluated atrial conduction, diastolic function, endothelial function, and systemic inflammation in early-onset PAF patients without structural heart disease or overt comorbidities. Methods: In this cross-sectional study, 40 patients aged 18–65 years with documented early-onset PAF were compared with 40 age and sex matched healthy individuals in sinus rhythm. All subjects underwent measurement of P wave dispersion and signal-averaged P wave duration, echocardiographic assessment of diastolic parameters, evaluation of endothelial function using flow-mediated dilation (FMD), and analysis of systemic inflammation via high-sensitivity C-reactive protein (hsCRP). Results: Patients with PAF demonstrated significantly increased P wave dispersion (51.63 ± 11.17 ms vs. 35.13 ± 6.15 ms; p < 0.001) and prolonged signal-averaged P wave duration (146.75 ± 19.68 ms vs. 124.40 ± 9.05 ms; p < 0.001). Diastolic dysfunction was evident, characterized by a reduced E/A ratio and elevated septal E/E′. Left atrial volume index was significantly higher in the PAF group (29.79 ± 3.94 mL/m² vs. 28.23 ± 1.74 mL/m²; p = 0.025). Endothelial function was impaired, as reflected by lower FMD values (5.27 ± 1.94% vs. 6.65 ± 1.78%; p = 0.001), while hsCRP levels were significantly higher in the PAF group (0.40 [0.30–0.55] vs. 0.24 [0.20–0.30] mg/dL; p < 0.001). Multivariate analysis identified signal-averaged P wave duration, P wave dispersion, mitral E wave velocity, septal E/E′, and left atrial volume index as independent predictors of PAF. Conclusion: Even in the absence of overt cardiovascular disease, early-onset PAF is associated with meaningful disturbances in atrial conduction, diastolic performance, endothelial function, and systemic inflammation. These findings support the presence of early atrial cardiomyopathy and underscore the need for comprehensive cardiovascular evaluation in younger PAF patients.